Optimized billet-production scheduling for an aluminium casting house - Garðar Ingi Reynisson 1987- (2017)
This research investigates the potential of time savings in the production process of an aluminium smelter in Iceland, i.e. the Rio Tinto Alcan aluminium smelter called ISAL. The focus was on the casting house. A mixed integer linear optimization model was developed to propose the optimal production schedule for each production week, based on the customer's demands. The model minimizes the mould exchanges for the casting machines and controls the mass of raw material in each production period by using chemical analysis. It was essential to track the usage of raw material because the furnaces cannot be emptied completely in each period and there are always some residues left in the furnaces. The ingredients of each cast must fit between certain upper and lower limits of each element to fulfil quality standards. Given that fact, it's essential to consider the residues in the furnace where upcoming alloy is fabricated. Otherwise the cast is ruined. The model was tested for two different production weeks from 2016. The first week can be considered as a typical production week but the latter is more challenging. The optimization model was able to return an applicable production schedule for the first week but the production schedule for the latter week was very close being applicable. % for both cases. Í þessu verkefni var kannað hvort hægt væri að ná fram tímasparnaði í framleiðsluferli Álversins í Straumsvík, nánar tiltekið innan steypuskálans. Þróað var línulegt bestunarlíkan, þ.e. blandað heiltölulíkan, til þess að reikna út hagstæðasta framleiðsluskipulag fyrir hverja framleiðsluviku. Líkanið tekur inn pantanir fyrir heila framleiðsluviku og skilar uppröðun af hagstæðasta framleiðsluskipulagi. Bestunarlíkanið lágmarkar heildarfjölda mótaskipta í hverri framleiðsluviku ásamt því að stýra hráefnisnotkun við framleiðsluna með efnagreiningu. Nauðsynlegt þótti að taka sérstakt tillit til hráefnisnotkunarinnar vegna þess að ekki er hægt að tæma allt innihald úr íblöndunarofnunum í hverri framleiðslulotu. Þar af ...